The Effectiveness of Public Service Digitalization Policies in Enhancing Transparency: Evidence from Digital Governance Implementation - Andre Putra Hermanto; Elvira Safitri; Winda Sari (IHSA Institute, 2026)
The digital transformation of public services has become a key strategy for improving governance, particularly in enhancing transparency and accountability. This study aims to analyze the effectiveness of public service digitalization policies in increasing transparency, identify the factors influencing their implementation, and evaluate the gap between expected and actual outcomes. The research employs a mixed-methods approach, combining quantitative data collected through questionnaires distributed to public service users and qualitative data obtained from interviews with government officials and document analysis of relevant policies and reports. The findings indicate that digitalization policies have a positive impact on transparency, particularly in improving access to information and enabling users to monitor service processes. However, the overall level of effectiveness is categorized as moderate, as the benefits are not evenly distributed and are influenced by several factors, including technology readiness, human resource capacity, infrastructure availability, and digital literacy. The study also reveals a gap between the expected outcomes of digitalization such as full transparency and seamless service integration and the actual implementation, which is often constrained by fragmented systems, incomplete information, and limited accessibility. In conclusion, while digitalization has significant potential to enhance transparency in public services, its effectiveness depends on comprehensive implementation and supportive conditions. The study recommends strengthening policy integration, improving system design, expanding infrastructure, and enhancing digital competencies to achieve more optimal transparency outcomes. These findings contribute to the development of digital governance practices and provide insights for policymakers and researchers in the field of public administration.